Black, Indigenous, People of Color and Feelings of Safety in School: Decomposing Variation and Ecological Assets - Samantha Viano; Natalie Truong (SAGE Publishing, 2022)
Feeling unsafe at school undermines student well-being and educational outcomes. Black, Indigenous, People of Color (BIPOC) might feel less safe at school due to attending systemically inequitable schools and discriminatory treatment. This QuantCrit study examines two facets of this inequality of opportunity: factors explaining differing rates of feeling unsafe and ecological assets of BIPOC students. Methods include decomposition to understand differences in feelings of safety and structural equation modeling to examine relationships between safety, ecological assets, and subsequent outcomes, using data from two nationally represented, longitudinal data sets. We find that BIPOC students felt less safe at school than did White students, and these differences are more attributable to variation between schools for Black students and within-school differences for Hispanic and American Indian students. The association between feeling unsafe and early adulthood socioeconomic status was fully mediated by ecological assets for Black and Hispanic students, but only partially mediated for White students.